2022
DOI: 10.1111/dome.12269
|View full text |Cite
|
Sign up to set email alerts
|

Colors and Orientalism as associations: Exploring the semiotic (re)presentation of Saudi women in British and Saudi newspapers

Abstract: Media representations can have significant influence in shaping opinions and influence public response to certain communities or gender and ethnic representations around the world. Investigating semiotic representation in linguistic discourse as vehicles for meaning in culture has been a fruitful area of research over the past decades. This study explores how stereotypes of women feed into the representations of Saudi women in contemporary press in Britain and Saudi Arabia. The focus is on the newspaper genre.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…While most research on media representations of Saudi women has analysed texts, Elyas et al (2022) conducted a small-scale visual analysis comparing the UK and SA press. The study concluded that black colour dominated the representations of Saudi women in British newspapers, whereas in the SA press, black attire was barely noticeable and Saudi women were depicted more frequently as active social agents.…”
Section: Saudi Women Representations In the Newsmentioning
confidence: 99%
See 1 more Smart Citation
“…While most research on media representations of Saudi women has analysed texts, Elyas et al (2022) conducted a small-scale visual analysis comparing the UK and SA press. The study concluded that black colour dominated the representations of Saudi women in British newspapers, whereas in the SA press, black attire was barely noticeable and Saudi women were depicted more frequently as active social agents.…”
Section: Saudi Women Representations In the Newsmentioning
confidence: 99%
“…Yet, the triangulations have included mostly one mode, that is, written language (including transcriptions). There are several corpus linguists who have recognized the importance of other modes of communication (e.g., Adolphs & Carter, 2015;Knight, 2011), and some have already integrated the visual mode into corpus linguistics (Caple et al, 2020;Elyas et al, 2022;Sun & Chalupnik, 2022). The latter group often limits the 3 amount of images to be studied considerably, partially because of the complexity of visuals.…”
Section: Introductionmentioning
confidence: 99%